Characterization of Ruminococcus albus cellodextrin phosphorylase and identification of a key phenylalanine residue for acceptor specificity and affinity to the phosphate group. (19th July 2013) - Sawano, Tatsuya; Saburi, Wataru; Hamura, Ken; Matsui, Hirokazu; Mori, Haruhide
Abstract : Ruminococcus albus has the ability to intracellularly degrade cello‐oligosaccharides primarily via phosphorolysis. In this study, the enzymatic characteristics of R. albus cellodextrin phosphorylase (RaCDP), which is a member of glycoside hydrolase family 94, was investigated. RaCDP catalyzes the phosphorolysis of cellotriose through an ordered 'bi bi' mechanism in which cellotriose binds to RaCDP before inorganic phosphate, and then cellobiose and glucose 1‐phosphate (Glc1 P ) are released in that order. Among the cello‐oligosaccharides tested, RaCDP had the highest phosphorolytic and synthetic activities towards cellohexaose and cellopentaose, respectively. RaCDP successively transferred glucosyl residues from Glc1 P to the growing cello‐oligosaccharide chain, and insoluble cello‐oligosaccharides comprising a mean of eight residues were produced. Sophorose, laminaribiose, β‐1, 4‐xylobiose, β‐1, 4‐mannobiose and cellobiitol served as acceptors for RaCDP. RaCDP had very low affinity for phosphate groups in both the phosphorolysis and synthesis directions. A sequence comparison revealed that RaCDP has Gln at position 646 where His is normally conserved in the phosphate binding sites of related enzymes. A Q646H mutant showed approximately twofold lower apparent K m values for inorganic phosphate and Glc1 P than the wild‐type. RaCDP has Phe at position 633 corresponding to Tyr and Val in the +1 subsites of cellobiose phosphorylase and N, N ′‐diacetylchitobiose phosphorylase, respectively. A F633Y mutant showed higher preference for cellobiose over β‐1, 4‐mannobiose as an acceptor substrate in the synthetic reaction than the wild‐type. Furthermore, the F633Y mutant showed 75‐ and 1100‐fold lower apparent K m values for inorganic phosphate and Glc1 P, respectively, in phosphorolysis and synthesis of cellotriose. Abstract : R. albus cellodextrin phosphorylase (RaCDP), classified into glycoside hydrolase family 94, was characterized. Among the cello‐oligosaccharides tested, RaCDP had the highest phosphorolytic and synthetic activities towards cellohexaose and cellopentaose, respectively. Sophorose, laminaribiose, β‐1, 4‐xylobiose, β‐1, 4‐mannobiose, and cellobiitol served as acceptors. Site‐directed mutational study revealed that Tyr633 is responsible for low affinity to the phosphate group and synthetic activity towards β‐1, 4‐mannobiose.